Magnetic diploe interaction studied by the differential angular correlation method - Matthias, E.; Bôstrom, L.; Alice Maciel, M.; Salomon, M.; Lindqvist, T. (North Holland Publishing, 1963)
Fil: Matthias, E. Institute of Physics, University of Uppsala; Suecia